Calcium-tin co-doped O3 type sodium ion battery positive electrode material and preparation method thereof
Through the positive electrode material of O3-type sodium ion battery co-doped with calcium and tin, the problem of complex phase change and slow kinetics of O3-type layered transition metal oxide material during charging and discharging is solved, and the cycle stability and electricity of the material are improved Chemical properties extend battery life.
Patent Information
- Application Number
- CN202411412001.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-10
AI Technical Summary
During the charging and discharging process, O3 layered transition metal oxide materials have complex phase transition and slow kinetics, resulting in rapid decline in capacity and reduced energy density. The large radius of sodium ions makes it difficult to embed and remove, resulting in short battery cycle life. .
Using calcium-tin co-doping strategy, by introducing Sn4+ into the transition metal layer and Ca2+ into the sodium layer, it can stabilize the layered oxide structure, inhibit the slippage of the transition metal layer during sodium ion deintercalation, and support the sodium ions. The transmission path improves the structural and chemical stability of the material.
The cycle stability and cycle life of the material are significantly improved, while maintaining a considerable discharge specific capacity, extending battery life, and reducing stress accumulation through a mild phase change process, improving electrochemical performance.
Smart Images

Figure CN119297265A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion battery positive electrode materials, and specifically relates to an O3 type sodium ion battery layered positive electrode material and a preparation method thereof. Background Art
[0002] With the continuous consumption of fossil energy around the world, there is an urgent need to incorporate clean energy such as wind energy and solar energy into energy storage systems. Among all energy storage technologies, rechargeable battery technology that can directly power electronic power equipment has received great attention. Among them, lithium-ion batteries have been widely used in portable electronic devices such as mobile phones and laptops, new energy vehicles, and energy storage systems due to their advantages such as high energy density and long cycle life. However, the shortage of lithium resources (the content of lithium in the earth's crust is 0.0017 wt%) has become a focus of attention around the world. Therefore, considering its price cost and limited application in large-scale energy storage, it is necessary to find another low-cost alternative.
[0003] The abundance, easy access and low cost of sodium resources have led to the rapid development of sodium-ion battery technology, and the industrialization process in the fields of energy storage and small power is also advancing rapidly. The positive electrode material is the core component of the battery. At present, the positive electrode materials of sodium-ion batteries can be divided into layered transition metal oxides, Prussian blue and polyanions. Among them, layered transition metal oxide positive electrode materials are considered to be more ideal positive electrode materials for sodium-ion batteries due to their simple structure, easy synthesis and high average working voltage. Layered transition metal oxide materials for sodium-ion batteries can be divided into P2, O3 and other crystal forms. Compared with P2 materials, O3 materials have the advantages of higher initial sodium content and high capacity. However, due to the complex phase change and slow kinetics during the charge and discharge process of O3 layered transition metal oxide materials, their capacity will drop rapidly and their energy density will decrease.
[0004] Ion doping has been shown to solve the above problems by stabilizing the crystal structure to improve the overall structural / chemical stability. For example, Liu et al. synthesized NaNi by ball milling-spray drying. 0.325 Fe 0.33 Mn 0.33 Zn 0.005 O2 cathode material has a voltage range of 2.0~4.0 V and a capacity of 130 mA g ﹣1 The current density is 117 mAh g ﹣1 The specific capacity of the material was 86.53% after 200 cycles (Electrochimica Acta 2022, 418, 140357). Li et al. synthesized Na 0.9 Ca 0.05 Ni0.33 Fe 0.33 Mn 0.33 O2 cathode material in the voltage range of 2.0~4.0 V 130 mAg ﹣1 The current density is 104.40 mAh g ﹣1 The specific capacity of the material is 87.65% after 200 cycles (Journal of Alloys and Compounds 2024, 976, 172977). The above strategies improve the electrochemical performance of the material, but its specific capacity is low and the capacity retention rate needs to be further improved.
[0005] Although some progress has been made in the research of layered oxides for sodium-ion batteries, there are still some challenges and problems to be solved. The large radius of sodium ions makes it more difficult for them to be embedded in and extracted from electrode materials, resulting in a shorter cycle life of the battery. Therefore, it is still necessary to continue to develop O3-type layered transition metal oxide materials with higher capacity and stability in the future to realize their application in the field of energy storage. Summary of the invention
[0006] The purpose of the present invention is to provide a calcium-tin co-doped O3 type sodium ion battery positive electrode material and a preparation method thereof in view of the shortcomings of the current technology. 4+ The transition metal layer doped into the positive electrode material uses its strong metal oxygen bond with high bond energy and high stability to inhibit the slip of the transition metal layer during the sodium ion extraction process and effectively stabilize the layered oxide structure. 2+ Doped into the sodium layer of the positive electrode material, in Na + After being detached, the rivet is fixed to the alkali metal layer, acting as a pillar to stabilize the transmission path of sodium ions, thus improving the stability of the material and ensuring the Na + Due to the normal diffusion of calcium and tin co-doping, the material not only has a discharge specific capacity comparable to that of the original material, but also improves the structural stability and cycle stability during the cycle, thereby extending the battery life.
[0007] To achieve the above object, the technical solution of the present invention is as follows: A calcium-tin co-doped O3 type sodium ion battery positive electrode material, the chemical formula of the positive electrode material is Na 1- 2x Ca x Ni 0.33 Fe 0.33 Mn 0.33-y Sn y O2, 0 < x ≤ 0.025, 0 < y≤ 0.02, the subscripts are the theoretical atomic ratios between the elements.
[0008] The x is preferably 0.01; and the y is preferably 0.015.
[0009] The method for preparing the calcium-tin co-doped O3 type sodium ion battery positive electrode material comprises the following steps: (1) mixing and grinding a sodium source, a calcium source, a nickel source, an iron source, a manganese source and a tin source to obtain a precursor mixture; (2) The precursor mixture is heated to 400-500°C at a heating rate of 3-6°C / min and calcined for 3-7 h, and then heated to 800-1000°C at a heating rate of 3-6°C / min and calcined for 10-15 h. After cooling, a calcium and tin doped O3 type sodium ion battery layered oxide positive electrode material is obtained.
[0010] The sodium source in step (1) is one of sodium hydroxide, sodium carbonate, sodium acetate, sodium nitrate and sodium sulfate.
[0011] The calcium source in step (1) is one of calcium oxide, calcium carbonate, calcium chloride, calcium fluoride and calcium sulfate.
[0012] The nickel source in step (1) is one of nickel oxide, nickel hydroxide, nickel acetate, nickel nitrate, nickel sulfate and nickel carbonate.
[0013] The iron source in step (1) is one of ferric oxide, ferric hydroxide and ferric acetate.
[0014] The manganese source in step (1) is one of manganese dioxide, manganese carbonate, manganese monoxide and manganese acetate.
[0015] The tin source in step (1) is one of tin oxide, tin hydroxide, tin acetate, tin nitrate, tin sulfate and tin carbonate.
[0016] The grinding in step (1) is ball milling with a rotation speed of 800-1000 r / min and a time of 10-13 h.
[0017] The grinding agent used in the grinding described in step (1) is anhydrous ethanol or acetone.
[0018] The application of the calcium-tin co-doped O3 type sodium ion battery positive electrode material is used as a positive electrode material in a sodium ion battery.
[0019] Specifically: the O3 type sodium ion battery layered oxide positive electrode material is mixed with conductive carbon black (Super P) and binder (PVDF) in a mass ratio of 8:1:1, and then N-methylpyrrolidone (NMP) is added. The evenly stirred slurry is coated on aluminum foil with a coating thickness of 50-150 μm, and dried to obtain a working electrode as the positive electrode. The selected negative electrode is metallic sodium, the electrolyte is commercial 1 mol / L NaClO4 / EC:PC:EMC (1:1:1) + 2% FEC, and the diaphragm is a glass fiber membrane GF-A diaphragm.
[0020] The beneficial effects of the present invention are: (1) The present invention uses a solid phase method to synthesize the target layered oxide positive electrode material. No special atmosphere protection is required during the preparation process, the synthesis process is simple, and the production efficiency is high. In addition, all raw materials of the present invention are easily available, non-toxic, widely available, and low-cost, and are suitable for large-scale mass production.
[0021] (2) The present invention adopts a double doping strategy of trace metal ions to dope Sn, which has a strong binding force with oxygen. 4+ Doping transition metal layer, Ca 2+ The addition of alkali metal layer causes the material to undergo a milder phase transition process, reduces the accumulation of stress during the sodium ion extraction process, inhibits the structural damage caused by the slip of the transition metal layer, and improves the stability of the material. 2+ and Sn 4+ Successfully doped into the crystal structure of the positive electrode material without any effect on the crystal structure, wherein the preferred Na 0.98 Ca 0.01 Ni 0.33 Fe 0.33 Mn 0.315 Sn 0.015 The O2 cathode material exhibits excellent electrochemical performance in the charge-discharge reaction process in the voltage range of 2.0-4.0 V. ﹣ At a current density of 1, the discharge reversible specific capacity is 125.08 mAh g ﹣1 The capacity retention rate reached 80.91% after 500 cycles, which has the potential for electrochemical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 In Example 1, Na 0.98 Ca 0.01 Ni 0.33 Fe 0.33 Mn 0.315 Sn 0.015 XRD pattern of O2 positive electrode material.
[0023] Figure 2 In Example 1, Na0.98 Ca 0.01 Ni 0.33 Fe 0.33 Mn 0.315 Sn 0.015 Scanning electron microscope image of O2 positive electrode material.
[0024] Figure 3 In Example 1, Na 0.98 Ca 0.01 Ni 0.33 Fe 0.33 Mn 0.315 Sn 0.015 O2 cathode material in the voltage range of 2.0~4.0 V 150 mA g -1 The charge and discharge curves for the first three weeks under the current density.
[0025] Figure 4 In Example 1, Na 0.98 Ca 0.01 Ni 0.33 Fe 0.33 Mn 0.315 Sn 0.015 O2 cathode material in the voltage range of 2.0~4.0 V 150 mA g -1 Cycling curves for 500 cycles at the same current density.
[0026] Figure 5 For Comparative Example 1, NaNi 0.33 Fe 0.33 Mn 0.33 XRD pattern of O2 positive electrode material.
[0027] Figure 6 For Comparative Example 1, NaNi 0.33 Fe 0.33 Mn 0.33 Scanning electron microscope image of O2 positive electrode material.
[0028] Figure 7 For Comparative Example 1, NaNi 0.33 Fe 0.33 Mn 0.33 O2 cathode material 150 mAg in the voltage range of 2.0~4.0 V ﹣1 The charge and discharge curves for the first three weeks under the current density.
[0029] Figure 8 For Comparative Example 1, NaNi 0.33 Fe 0.33 Mn 0.33 O2 cathode material 150 mAg in the voltage range of 2.0~4.0 V ﹣1 Cycling curves for 500 cycles at the same current density. DETAILED DESCRIPTION
[0030] The present invention is further described in detail by combining the drawings and specific embodiments.
[0031] If no specific experimental conditions are specified in the following embodiments, conventional experimental conditions or experimental conditions recommended by the reagent company are generally followed. The materials and reagents used, unless otherwise specified, are all reagents and materials obtained from commercial sources.
[0032] Embodiment 1: (1) Mixed grinding: 1.03 mmol sodium carbonate (5 wt% excess to cope with the loss during high-temperature calcination, the same as in the following examples), 0.02 mmol calcium carbonate, 0.66 mmol nickel oxide, 0.33 mmol ferric oxide, 0.63 mmol manganese dioxide, and 0.03 mmol tin dioxide were added to an agate ball mill with a ball-to-material ratio of 20:1, and 3 ml of anhydrous ethanol and ball milling beads (diameter 5-9 mm) were added. The mixture was ball milled at a ball milling speed of 900 r / min for 12 h to obtain a uniformly mixed slurry; (2) Sintering reaction: The powdered precursor was placed in a muffle furnace, heated to 450°C at a heating rate of 5°C / min and calcined for 5 h, then heated to 900°C at a heating rate of 5°C / min and calcined for 15 h. It was then placed in an argon atmosphere glove box and cooled and ground to obtain a product with a theoretical molar ratio of Na 0.98 Ca 0.01 Ni 0.33 Fe 0.33 Mn 0.315 Sn 0.015 O2, Figure 1 This is the XRD pattern of the positive electrode material obtained in Example 4. Compared with the standard PDF card (PDF#54-0887), it can be seen that its structure belongs to the hexagonal system with space group R-3 m, corresponding to the O3 phase. Figure 2 This is a scanning electron microscope image of the positive electrode material obtained in Example 1, which is composed of particles of uneven sizes, and the particle size range is between 200 nm and 1 μm.
[0033] (3) Preparation of sodium ion battery: Weigh 80 mg of the positive electrode material prepared above, 10 mg of conductive carbon black (SuperP) and 10 mg of binder (PVDF), add 10 drops of N-methylpyrrolidone (NMP) to mix them evenly, apply the evenly stirred slurry onto aluminum foil with a coating thickness of 100 μm, and dry to obtain a working electrode as the positive electrode. The selected negative electrode is metallic sodium, the electrolyte is commercial 1 mol / L NaClO4 / EC:PC:EMC (1:1:1) + 2% FEC, and the diaphragm is a glass fiber membrane GF-A diaphragm.
[0034] The battery prepared in this example was subjected to a charge and discharge capacity test: the charge and discharge test was performed at room temperature using a Land CT2001A battery testing system. Figure 3 The positive electrode material obtained in Example 1 has a voltage range of 2.0-4.0 V and a capacitance of 150 mA g ﹣1 The charge and discharge curves of the first three weeks under the current density are shown in the figure. The discharge capacity of the first week is 125.53 mAh g ﹣1 , has a higher specific capacity. Figure 4 The positive electrode material obtained in Example 1 has a voltage range of 2.0-4.0 V and a capacity of 150 mA g ﹣1 The cycle curve of 500 cycles under the current density shows that the capacity retention rate is 87.38% after 300 cycles and 80.91% after 500 cycles, which has good cycle stability. Its good electrochemical performance may be due to the Ca 2+ and Sn 4+ The incorporation of makes the phase transition of the material more gentle, reduces the accumulation of stress and strain during the sodium ion insertion and extraction process, inhibits the structural damage caused by the slip of the transition metal layer, and improves the stability of the material.
[0035] Embodiment 2: (1) Mixed grinding: 1.01 mmol sodium carbonate (5 wt% excess), 0.05 mmol calcium carbonate, 0.66 mmol nickel oxide, 0.33 mmol iron oxide, 0.63 mmol manganese dioxide, and 0.03 mmol tin dioxide were added to an agate ball mill with a ball-to-material ratio of 20:1. 3 ml of anhydrous ethanol and ball milling beads (diameter 5-9 mm) were added and the mixture was ball milled at a ball mill speed of 900 r / min for 12 h to obtain a uniformly mixed slurry. (2) Sintering reaction: The powdered precursor was placed in a muffle furnace, heated to 450°C at a heating rate of 5°C / min and calcined for 5 h, then heated to 900°C at a heating rate of 5°C / min and calcined for 15 h. It was then placed in an argon atmosphere glove box and cooled and ground to obtain a product with a theoretical molar ratio of Na 0.95 Ca 0.025 Ni 0.33 Fe 0.33 Mn 0.315 Sn 0.015 O2, the obtained positive electrode material belongs to the hexagonal system with space group R-3 m, corresponding to the O3 phase.
[0036] (3) Preparation of sodium ion battery: Weigh 80 mg of the positive electrode material prepared above, 10 mg of conductive carbon black (SuperP) and 10 mg of binder (PVDF), add 10 drops of N-methylpyrrolidone (NMP) to mix them evenly, apply the evenly stirred slurry onto aluminum foil with a coating thickness of 100 μm, and dry to obtain a working electrode as the positive electrode. The selected negative electrode is metallic sodium, the electrolyte is commercial 1 mol / L NaClO4 / EC:PC:EMC (1:1:1) + 2% FEC, and the diaphragm is a glass fiber membrane GF-A diaphragm.
[0037] The battery prepared in this example was tested for charge and discharge capacity: the charge and discharge test was performed at room temperature using a Land CT2001A battery test system. The positive electrode material obtained had a charge and discharge capacity of 150 mA g in the voltage range of 2.0-4.0 V. ﹣1 The first cycle discharge capacity at this current density is 132.27 mAh g ﹣1 The specific capacity is high, the capacity retention rate is 83.40% after 300 cycles, and the capacity retention rate is 69.88% after 500 cycles, and the cycle stability is poor.
[0038] Comparative Example 1: (1) Mixed grinding: Add 1.05 mmol sodium carbonate (5 wt% excess), 0.66 mmol nickel oxide, 0.33 mmol ferric oxide, and 0.66 mmol manganese dioxide into an agate ball mill with a ball-to-material ratio of 20:1, and add 3 ml of anhydrous ethanol and ball milling beads (diameter 5-9 mm) and mix them at a speed of 900 r / min for 12 h to obtain a uniformly mixed slurry; dry the slurry to obtain a powdery precursor; (2) Sintering reaction: The powdered precursor was placed in a muffle furnace, heated to 450°C at a heating rate of 5°C / min and calcined for 5 h, then heated to 900°C at a heating rate of 5°C / min and calcined for 15 h. It was then placed in an argon atmosphere glove box and cooled and ground to obtain a product with a theoretical molar ratio of NaNi 0.33 Fe 0.33 Mn 0.33 O2, Figure 5 This is the XRD pattern of the positive electrode material obtained in Comparative Example 1. Compared with the standard PDF card (PDF#54-0887), it can be seen that its structure belongs to the hexagonal crystal system with space group R-3 m, corresponding to the O3 phase. Figure 6 This is a scanning electron microscope image of the positive electrode material obtained in Comparative Example 1, which is composed of particles of uneven sizes, and the particle size range is between 200 nm and 1 μm.
[0039] (3) Preparation of sodium ion battery: Weigh 80 mg of the positive electrode material prepared above, 10 mg of conductive carbon black (SuperP) and 10 mg of binder (PVDF), add 10 drops of N-methylpyrrolidone (NMP) to mix them evenly, apply the evenly stirred slurry onto aluminum foil with a coating thickness of 100 μm, and dry to obtain a working electrode as the positive electrode. The selected negative electrode is metallic sodium, the electrolyte is commercial 1 mol / L NaClO4 / EC:PC:EMC (1:1:1) + 2% FEC, and the diaphragm is a glass fiber membrane GF-A diaphragm.
[0040] The battery prepared in this comparative example was subjected to a charge and discharge capacity test: the charge and discharge test was conducted at room temperature using a Land CT2001A battery testing system. Figure 7 The positive electrode material obtained in Comparative Example 1 has a voltage range of 2.0-4.0 V and a capacitance of 150 mA g ﹣1 The charge and discharge curves of the first three weeks under the current density are shown in the figure. The discharge capacity of the first week is 132.53 mAh g ﹣1 , has a higher specific capacity. Figure 8 The positive electrode material obtained in Comparative Example 1 has a voltage range of 2.0-4.0 V and a capacitance of 150 mA g ﹣1 The cycle curve of 500 cycles under current density shows that the capacity retention rate is 62.72% after 300 cycles and 38.35% after 500 cycles. The cycle stability is poor. The poor electrochemical performance may be because the accumulated stress and strain after long-term cycling destroys the structure of the material and affects the normal insertion and extraction of sodium ions.
[0041] Comparative Example 2: (1) Mixed grinding: 1.05 mmol sodium carbonate (5 wt% excess), 0.66 mmol nickel oxide, 0.33 mmol ferric oxide, 0.64 mmol manganese dioxide, and 0.02 mmol tin dioxide were added to an agate ball mill with a ball-to-material ratio of 20:1. 3 ml of anhydrous ethanol and ball mill beads (diameter 5-9 mm) were added and the mixture was ball milled at a speed of 900 r / min for 12 h to obtain a uniformly mixed slurry. The slurry was dried to obtain a powdery precursor. (2) Sintering reaction: The powdered precursor was placed in a muffle furnace, heated to 450°C at a heating rate of 5°C / min and calcined for 5 h, then heated to 900°C at a heating rate of 5°C / min and calcined for 15 h. It was then placed in an argon atmosphere glove box and cooled and ground to obtain a product with a theoretical molar ratio of NaNi 0.33 Fe 0.33 Mn 0.32 Sn 0.01O2, the obtained positive electrode material belongs to the hexagonal system with space group R-3 m, corresponding to the O3 phase.
[0042] (3) Preparation of sodium ion battery: Weigh 80 mg of the positive electrode material prepared above, 10 mg of conductive carbon black (SuperP) and 10 mg of binder (PVDF), add 10 drops of N-methylpyrrolidone (NMP) to mix them evenly, apply the evenly stirred slurry onto aluminum foil with a coating thickness of 100 μm, and dry to obtain a working electrode as the positive electrode. The selected negative electrode is metallic sodium, the electrolyte is commercial 1 mol / L NaClO4 / EC:PC:EMC (1:1:1) + 2% FEC, and the diaphragm is a glass fiber membrane GF-A diaphragm.
[0043] The battery prepared in this comparative example was tested for charge and discharge capacity: the charge and discharge test was performed at room temperature using a Land CT2001A battery test system. The obtained positive electrode material had a capacity of 150 mA g in the voltage range of 2.0-4.0 V. ﹣1 The first cycle discharge capacity at the current density is 122.21 mAh g ﹣1 The capacity retention rate after 300 cycles is 77.40%.
[0044] Comparative Example 3: (1) Mixed grinding: 1.05 mmol sodium carbonate (5 wt% excess), 0.66 mmol nickel oxide, 0.33 mmol iron oxide, 0.63 mmol manganese dioxide, and 0.03 mmol tin dioxide were added to an agate ball mill with a ball-to-material ratio of 20:1. 3 ml of anhydrous ethanol and ball mill beads (diameter 5-9 mm) were added and the mixture was ball milled at a ball mill speed of 900 r / min for 12 h to obtain a uniformly mixed slurry. The slurry was dried to obtain a powdery precursor. (2) Sintering reaction: The powdered precursor was placed in a muffle furnace, heated to 450°C at a heating rate of 5°C / min and calcined for 5 h, then heated to 900°C at a heating rate of 5°C / min and calcined for 15 h. It was then placed in an argon atmosphere glove box and cooled and ground to obtain a product with a theoretical molar ratio of NaNi 0.33 Fe 0.33 Mn 0.315 Sn 0.015 O2, the obtained positive electrode material belongs to the hexagonal system with space group R-3 m, corresponding to the O3 phase.
[0045] (3) Preparation of sodium ion battery: Weigh 80 mg of the positive electrode material prepared above, 10 mg of conductive carbon black (SuperP) and 10 mg of binder (PVDF), add 10 drops of N-methylpyrrolidone (NMP) to mix them evenly, apply the evenly stirred slurry onto aluminum foil with a coating thickness of 100 μm, and dry to obtain a working electrode as the positive electrode. The selected negative electrode is metallic sodium, the electrolyte is commercial 1 mol / L NaClO4 / EC:PC:EMC (1:1:1) + 2% FEC, and the diaphragm is a glass fiber membrane GF-A diaphragm.
[0046] The battery prepared in this comparative example was tested for charge and discharge capacity: the charge and discharge test was performed at room temperature using a Land CT2001A battery test system. The obtained positive electrode material had a capacity of 150 mA g in the voltage range of 2.0-4.0 V. ﹣1 The first cycle discharge capacity at this current density is 129.91 mAh g ﹣1 The capacity retention rate after 300 cycles is 76.85%.
[0047] Comparative Example 4: (1) Mixed grinding: 1.05 mmol sodium carbonate (5 wt% excess), 0.66 mmol nickel oxide, 0.33 mmol ferric oxide, 0.62 mmol manganese dioxide, and 0.04 mmol tin dioxide were added to an agate ball mill with a ball-to-material ratio of 20:1. 3 ml of anhydrous ethanol and ball milling beads (diameter 5-9 mm) were added and the mixture was ball milled at a speed of 900 r / min for 12 h to obtain a uniformly mixed slurry. The slurry was dried to obtain a powdery precursor. (2) Sintering reaction: The powdered precursor was placed in a muffle furnace, heated to 450°C at a heating rate of 5°C / min and calcined for 5 h, then heated to 900°C at a heating rate of 5°C / min and calcined for 15 h. It was then placed in an argon atmosphere glove box and cooled and ground to obtain a product with a theoretical molar ratio of NaNi 0.33 Fe 0.33 Mn 0.31 Sn 0.02 O2, the obtained positive electrode material belongs to the hexagonal system with space group R-3 m, corresponding to the O3 phase.
[0048] (3) Preparation of sodium ion battery: Weigh 80 mg of the positive electrode material prepared above, 10 mg of conductive carbon black (SuperP) and 10 mg of binder (PVDF), add 10 drops of N-methylpyrrolidone (NMP) to mix them evenly, apply the evenly stirred slurry onto aluminum foil with a coating thickness of 100 μm, and dry to obtain a working electrode as the positive electrode. The selected negative electrode is metallic sodium, the electrolyte is commercial 1 mol / L NaClO4 / EC:PC:EMC (1:1:1) + 2% FEC, and the diaphragm is a glass fiber membrane GF-A diaphragm.
[0049] The battery prepared in this comparative example was tested for charge and discharge capacity: the charge and discharge test was performed at room temperature using a Land CT2001A battery test system. The obtained positive electrode material had a capacity of 150 mA g in the voltage range of 2.0-4.0 V. ﹣1 The first cycle discharge capacity at this current density is 111.46 mAh g ﹣1 , the specific capacity is low, and the capacity retention rate after 300 cycles is 75.90%.
[0050] Comparative Example 5: (1) Mixed grinding: 1.03 mmol sodium carbonate (5 wt% excess), 0.02 mmol calcium carbonate, 0.66 mmol nickel oxide, 0.33 mmol iron oxide, and 0.66 mmol manganese dioxide were added to an agate ball mill with a ball-to-material ratio of 20:1. 3 ml of anhydrous ethanol and ball mill beads (diameter 5-9 mm) were added and the mixture was ball milled at a ball mill speed of 900 r / min for 12 h to obtain a uniformly mixed slurry. The slurry was dried to obtain a powdery precursor. (2) Sintering reaction: The powdered precursor was placed in a muffle furnace, heated to 450°C at a heating rate of 5°C / min and calcined for 5 h, then heated to 900°C at a heating rate of 5°C / min and calcined for 15 h. It was then placed in an argon atmosphere glove box and cooled and ground to obtain a product with a theoretical molar ratio of Na 0.98 Ca 0.01 Ni 0.33 Fe 0.33 Mn 0.33 O2, the obtained positive electrode material belongs to the hexagonal system with space group R-3 m, corresponding to the O3 phase.
[0051] (3) Preparation of sodium ion battery: Weigh 80 mg of the positive electrode material prepared above, 10 mg of conductive carbon black (SuperP) and 10 mg of binder (PVDF), add 10 drops of N-methylpyrrolidone (NMP) to mix them evenly, apply the evenly stirred slurry onto aluminum foil with a coating thickness of 100 μm, and dry to obtain a working electrode as the positive electrode. The selected negative electrode is metallic sodium, the electrolyte is commercial 1 mol / L NaClO4 / EC:PC:EMC (1:1:1) + 2% FEC, and the diaphragm is a glass fiber membrane GF-A diaphragm.
[0052] The battery prepared in this comparative example was tested for charge and discharge capacity: the charge and discharge test was performed at room temperature using a Land CT2001A battery test system. The obtained positive electrode material had a capacity of 150 mA g in the voltage range of 2.0-4.0 V. ﹣1 The first cycle discharge capacity at this current density is 123.52 mAh g ﹣1 The capacity retention rate after 300 cycles is 75.51%, and the capacity retention rate after 500 cycles is 62.79%.
[0053] Comparative Example 6: (1) Mixed grinding: 1.01 mmol sodium carbonate (5 wt% excess), 0.05 mmol calcium carbonate, 0.66 mmol nickel oxide, 0.33 mmol iron oxide, and 0.66 mmol manganese dioxide are added to an agate ball mill with a ball-to-material ratio of 20:1. 3 ml of anhydrous ethanol and ball mill beads (diameter 5-9 mm) are added and the mixture is ball milled at a ball mill speed of 900 r / min for 12 h to obtain a uniformly mixed slurry. The slurry is dried to obtain a powdery precursor. (2) Sintering reaction: The powdered precursor was placed in a muffle furnace, heated to 450°C at a heating rate of 5°C / min and calcined for 5 h, then heated to 900°C at a heating rate of 5°C / min and calcined for 15 h. It was then placed in an argon atmosphere glove box and cooled and ground to obtain a product with a theoretical molar ratio of Na 0.95 Ca 0.025 Ni 0.33 Fe 0.33 Mn 0.33 O2, the obtained positive electrode material belongs to the hexagonal system with space group R-3 m, corresponding to the O3 phase.
[0054] (3) Preparation of sodium ion battery: Weigh 80 mg of the positive electrode material prepared above, 10 mg of conductive carbon black (SuperP) and 10 mg of binder (PVDF), add 10 drops of N-methylpyrrolidone (NMP) to mix them evenly, apply the evenly stirred slurry onto aluminum foil with a coating thickness of 100 μm, and dry to obtain a working electrode as the positive electrode. The selected negative electrode is metallic sodium, the electrolyte is commercial 1 mol / L NaClO4 / EC:PC:EMC (1:1:1) + 2% FEC, and the diaphragm is a glass fiber membrane GF-A diaphragm.
[0055] The battery prepared in this example was tested for charge and discharge capacity: the charge and discharge test was performed at room temperature using the Land CT2001A battery test system. The positive electrode material obtained had a voltage range of 2.0-4.0 V at 150 mA g ﹣1 The first cycle discharge capacity at this current density is 122.18 mAh g ﹣1 The capacity retention rate after 300 cycles is 76.15%, and the capacity retention rate after 500 cycles is 64.78%.
[0056] Table 1 shows the half-cells assembled with the cathode materials obtained in each example at 150 mA g ﹣1 The first cycle discharge capacity under current density and the capacity retention rate after 300 and 500 cycles. The first cycle discharge capacity of Example 1 and Example 2 are 125.08 and 132.27 mAh·g, respectively. ﹣1 After 300 cycles, the discharge specific capacities are 108.80 and 109.99 mAh·g, respectively. ﹣1 After 500 cycles, the discharge specific capacities of the positive electrode materials of Example 1 and Example 2 were 100.75 and 92.16 mAh·g, respectively. ﹣1 The first cycle discharge specific capacities of comparative examples 1 to 6 are 132.53, 122.21, 129.91, 111.46, 123.52 and 122.18 mAh·g, respectively. ﹣1 After 300 cycles, the discharge specific capacities are 82.70, 94.99, 99.26, 85.27, 92.75 and 92.42 mAh·g, respectively. ﹣1 After 500 cycles, the discharge specific capacities of Comparative Example 1, Comparative Example 6 and Comparative Example 7 are 50.56, 77.13 and 78.61 mAh·g ﹣1 From the comparison of the above data, it can be seen that the co-doping of calcium and tin improves the cycle stability of the positive electrode material without losing much capacity.
[0057]
[0058] The present invention successfully prepares a long-cycle stable O3 type sodium ion battery layered oxide positive electrode material by controlling the element ratio through element doping strategy. By comparing the above implementation cases, it can be seen that the proposed type of O3 type sodium ion battery layered oxide positive electrode material has a high reversible capacity and a good cycle life.
[0059] Matters not covered by the present invention are known technologies.
Claims
1. A calcium-tin co-doped O3 type sodium ion battery positive electrode material, characterized by The chemical formula of the positive electrode material is Na 1- 2x Ca x Ni 0.33 Fe 0.33 Mn 0.33-y Sn y O2, 0 < x ≤ 0.025, 0 < y ≤ 0.02, the subscripts are the theoretical atomic ratios between the elements.
2. The calcium-tin co-doped O3 type sodium ion battery positive electrode material as described in claim 1, characterized in that x is 0.01; y is 0.
015.
3. The method for preparing the calcium-tin co-doped O3 type sodium ion battery positive electrode material according to claim 1, characterized in that the method comprises the following steps: (1) According to the material ratio in the chemical formula, a sodium source, a calcium source, a nickel source, an iron source, a manganese source and a tin source are mixed and ground to obtain a precursor mixture; (2) The precursor mixture is heated to 400-500°C at a heating rate of 3-6°C / min, calcined for 3-7 h, and then heated to 800-1000°C at a heating rate of 3-6°C / min, calcined for 10-15 h, and cooled to obtain a calcium and tin doped O3 type sodium ion battery layered oxide positive electrode material.
4. The method for preparing the calcium-tin co-doped O3 type sodium ion battery positive electrode material according to claim 1, characterized in that The sodium source in step (1) is sodium hydroxide, sodium carbonate, sodium acetate, sodium nitrate or sodium sulfate; The calcium source is calcium oxide, calcium carbonate, calcium chlorate, calcium fluoride or calcium sulfate; The nickel source is nickel oxide, nickel hydroxide, nickel acetate, nickel nitrate, nickel sulfate or nickel carbonate; The iron source is ferric oxide, ferric hydroxide or ferric acetate; The manganese source is manganese dioxide, manganese carbonate, manganese monoxide or manganese acetate; The tin source is tin oxide, tin hydroxide, tin acetate, tin nitrate, tin sulfate or tin carbonate; The grinding is ball milling, the rotation speed is 800-1000r / min, and the time is 10-13h; The grinding agent used for grinding is anhydrous ethanol or acetone.
5. The use of the calcium-tin co-doped O3 type sodium ion battery positive electrode material as claimed in claim 1, characterized in that it is used as a positive electrode material in a sodium ion battery.
6. The use of the calcium-tin co-doped O3 type sodium ion battery positive electrode material as claimed in claim 5, characterized in that: The O3 type sodium ion battery layered oxide positive electrode material is mixed with conductive carbon black (Super P) and binder (PVDF) in a mass ratio of 8:1:1, and then N-methylpyrrolidone (NMP) is added. The stirred slurry is coated on aluminum foil with a coating thickness of 50-150 μm and dried to obtain a working electrode as the positive electrode. The selected negative electrode is metallic sodium, the electrolyte is commercial 1 mol / L NaClO4 / EC:PC:EMC (1:1:1) + 2% FEC, and the diaphragm is a glass fiber membrane GF-A diaphragm.
Citation Information
Patent Citations
Metal ion doped and modified sodium ion positive electrode material as well as preparation method and application thereof
CN116409824A
O3 type sodium ion positive electrode material and preparation method and application thereof
CN117276521A
Abnormal O3 type sodium ion battery layered positive electrode material and preparation method thereof
CN117276530A
O3 type sodium electrode layered oxide electrode material and preparation method thereof
CN117865240A
Coagulant supply and mixing apparatus for sand production facility
KR1020220048903A
Cited By
Sodium ion battery positive electrode material with high rate and cycling stability, preparation method, positive electrode and sodium ion secondary battery
CN120497336A